The Impact of Syrian Displacement on the Water and Health Sector and Urban Change in Irbid, Jordan - Bani Khalaf, Amani Mohammad Salem; Kamarudin, Mohd Khairul Amri (Journal of Risk and Crisis Management, 2024)
The research conducted in Jordan's Irbid governorate focused on the impact of Syrian refugees on various sectors, including urbanization, water, and health services. The study highlighted the significant strain caused by the influx of refugees on basic services like water, health, and housing. Jordan, known for its limited water resources, faced challenges due to the increased demand from both its citizens and refugees. The study aimed to understand how Syrian asylum seekers affected these sectors and urbanization in Irbid.The findings revealed a substantial impact on basic services, with notable consequences such as increased water consumption, overcrowding in health centers, reduced medical service quality, insufficient healthcare facilities, and a housing crisis. The rise in land and housing prices by 200% posed challenges for both locals and refugees. The burden on the government led to changes in healthcare policies, transitioning from free treatment for Syrians to 80% coverage. Despite challenges, free services like thalassemia and maternal and child health remained available.The study employed a quantitative approach, distributing questionnaires to 563 randomly selected respondents across different regions in Irbid. The analysis using SPSS software confirmed the significant influence of Syrian refugees on the mentioned sectors. Specifically, the housing crisis in Irbid was exacerbated by soaring real estate prices, making it difficult for married couples to find affordable housing. To cope with rent burdens, refugees resorted to sharing accommodations with other families, leading to housing-related exploitation among citizens.
Keywords: Immigration; Asylum; Refugee